The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4756941
|View full text |Cite
|
Sign up to set email alerts
|

Angular-dependences of giant in-plane and interlayer magnetoresistances in Bi2Te3 bulk single crystals

Abstract: Angular-dependences of in-plane and interlayer magnetotransport properties in n-type Bi2Te3 bulk single crystals have been investigated over a broad range of temperatures and magnetic fields. Giant in-plane magnetoresistances (MR) of up to 500% and interlayer MR of up to 200% were observed, respectively. The observed MR exhibits quadratic field dependences in low fields and linear field dependences in high fields. The angular dependences of the MR represent strong anisotropy and twofold oscillations. The obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…Thus, the MR (%) value reduces from 440% to 150% as the temperature is increased from 5 K to 100 K. Moreover, as the field is changed from perpendicular to parallel the MR value reduces to 82% at 5 K under an applied magnetic field of 140 kOe. Further, the same reduces from 82% to 43% as the temperature is increased from 5 K to 100 K. Thus, we get a negligible value of MR in parallel component in comparison to the perpendicular component.Consequently, we can say that the MR is angular dependent [10,11,15]. Figure 5 represents the field derivative MR as a function of magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the MR (%) value reduces from 440% to 150% as the temperature is increased from 5 K to 100 K. Moreover, as the field is changed from perpendicular to parallel the MR value reduces to 82% at 5 K under an applied magnetic field of 140 kOe. Further, the same reduces from 82% to 43% as the temperature is increased from 5 K to 100 K. Thus, we get a negligible value of MR in parallel component in comparison to the perpendicular component.Consequently, we can say that the MR is angular dependent [10,11,15]. Figure 5 represents the field derivative MR as a function of magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ARPES experiments [42] Furthermore, the isotropic two-band mode cannot account for the four-fold angle dependence of the resistivity ρ(θ), as delineated in Fig.4(b). Although the surface states of a topological material such as SmB 6 could induce a similar four-fold angular magnetoresistance [61,62], the anisotropy in Fig.4(b) shows that nearly perfect four-fold symmetry should not arise from the crystal surfaces, since the crystal's width (223.33 μm) is much larger than its thickness (138.78 μm). ARPES experiments [42] have revealed that LaSb is topologically trivial.…”
Section: Iii2 Revealing the Bulk Origin Of The Shubnikov -De Haas Omentioning
confidence: 99%
“…It is also observed that the magnetoresistance in addition to being large is also linear and non-saturating. [17][18][19][20][21][22] Such large and linear magnetoresistance, which does not saturate even at high fields, was first observed in polycrystalline Bismuth and other metals by Kapitza 23,24 and this was explained by Lifshits 25 et al as due to open Fermi surfaces of the metals. However Bismuth has a small and closed Fermi surface.…”
Section: Introductionmentioning
confidence: 97%